Peran Good Corporate Governance Terhadap Profitabilitas Perbankan Syariah - Surepno, Surepno; Minoto, Minoto (AKTSAR: Jurnal Akuntansi Syariah, 2018)
This study aims to analyze and obtain empirical evidence of the contribution of Good Corporate Governance on return on assets (ROA) as a proxy of sharia banking profitability in the period of 2010-2016. Populations of this research are sharia commercial bank registered in Bank Indonesia in the period of 2010 to 2016. By using purposive sampling technique, there are 7 sharia banks from 13 sharia banks in Indonesia during the period of 2010-2016. Furthermore, research data is obtained from GCG reports that have been published by sharia banking in the period of 2010-2016. The data is analyzed by descriptive analysis and regression analysis. Results show that GCG not contribution for profitability proxied by ROA. Based on the results, it can be concluded that Good Corporate Governance does not affect the profitability of sharia banking. Good Corporate Governance in sharia banking is still not effective and efficient as described by high remuneration and special facilities received by the board in sharia banking.